Integrasi Manajemen Mutu di Lembaga Keuangan dan Publik - Zaen, Ekki Suryana; Azhaari, Hasna; Ramadhan, Rahmat; Nuriyah (IDARI: Jurnal Manajemen Dakwah, 2025)
Total Quality Management (TQM) is a holistic strategy crucial for enhancing service quality and organizational performance amidst strategic environmental shifts and digital transformation demands in both public and private sectors. This study critically analyzes the TQM implementation dynamics within Islamic Financial Institutions (IFIs) and public/private organizations in Indonesia, culminating in precise recommendations for refining Human Resource Management (HRM) practices. In IFIs, TQM is systematically interwoven with the foundational principles of Maqashid Syariah, serving as the ultimate customer-centric service benchmark and ensuring all internal processes are strictly aligned with ethical, spiritual, and social values. Digital innovations, particularly the Core Banking System (CBS) and integrated mobile banking platforms (e.g., BSI Mobile), function as TQM enablers by significantly boosting operational transparency (especially in contract disclosure) and process efficiency, directly improving customer satisfaction. Comprehensive cross-sector analysis (Gojek, BCA, BPJS Kesehatan) reveals that sustained quality integration is fundamentally dependent on three core factors: transformative strategic leadership that embeds a quality-first culture, rapid adaptation to disruptive digital technologies, and unwavering focus on operational excellence and customer orientation. The long-term rigidity and sustainability of TQM are predicated upon robust HRM. This requires value-based recruitment (value-fit), a comprehensive performance appraisal system that rigorously evaluates both process adherence and result achievement, and a systematically integrated reward mechanism to continuously reinforce the organizational quality culture. Utilizing Human Resource Information Systems (HRIS) is essential for monitoring and ensuring quality integrity across all organizational facets.